Fertility-Preserving Surgery in a Young Nulligravid Woman with Bilateral Coexistence of a Granulosa Cell Tumor with a Teratoma - Pham Ba Nha; Pham Van Tuyen; Nguyen Viet Ha; Nguyen Thi Thu Phuong (Case Reports in Obstetrics and Gynecology)
Background. The coexistence of a granulosa cell tumor with a teratoma is extremely rare and impossible to diagnose preoperatively. For most patients with advanced age and stage, the standard treatment is hysterectomy and bilateral salpingo-oophorectomy; however, fertility-preserving surgery should be considered for young nulligravid women. Case. We present a case of a 24-year-old nulligravid female with bilateral adnexal masses, imaging findings of ovarian teratomas, and normal levels of tumor markers. A laparotomy revealed bilateral dermoid cysts, and solid tissue invaded most of the remaining ovarian parenchyma with no signs of malignancy in the uterus and peritoneum space. Consequently, a bilateral oophorectomy was performed to preserve her fertility. Histopathology examination showed mature cystic teratomas coexisting with granulosa cell tumors on both ovaries. Within six months, there were no signs of recurrence on ultrasonography and tumor makers. Combined oral contraceptive pills were prescribed as hormone replacement therapy. Conclusion. Fertility-preserving surgery can be performed in young women with an ovarian granulosa cell tumor coexisting with a teratoma. Long-term examination, hormone replacement therapy, and in vitro fertilization are required.